AS PROFESSORAS DA ESCOLA D. MARIA : um estudo sobre identidade e docência na Educação Infantil - Coimbra, Kellen Regina Moraes (2011)
This study addresses the teaching of early childhood education, examining processes of identification and self-understanding of preschool teachers of the "School D. Mary "- public school early childhood education located in the outskirts of St. Louis from library research, discusses the possibilities and implications of identity categories for the analysis of teaching in early childhood education and historical and politically situated and teaching institutions for the care and education of the child. With this reasoning, provides and analyzes the data in empirical research, in which three teachers participated, through the development of narrative writing and individual and group interviews. Analysis of these data seeking to give meaning and significance to agents in their relations in the social world. Regarding the theoretical framework, the studies of Foucault (1984, 1995, 2008b; 2009th, 2009b), were of great importance, while reading the novel forms of subjugation practiced in modern societies. In the provision of results realize that teachers, especially in the education segment, are routinely asked to engage as responsible for a project to improve the school and the nation, are recipients of political actions implemented as manifestations of the state governing Modern (Foucault, 2007). Therefore, it elects the concepts of professionalism and training, as possible mechanisms of governance of the teachers, which takes place in that the teachers identify themselves to the ideals linked and may be denied by the strategies of resistance, for which teachers are positioned as subjects of history, historical, and politically situating their work and themselves.